Prospects to the formation and control of potential dimer impurity E of pantoprazole sodium sesquihydrate - Awasthi, Arun Kumar (J Pharm Anal, 2019)
Pantoprazole sodium, a substituted benzimidazole derivative, is an irreversible proton pump inhibitor which is primarily used for the treatment of duodenal ulcers, gastric ulcers, and gastroesophageal reflux disease (GERD). The monographs of European Pharmacopoeia (Ph. Eur.) and United States Pharmacopoeia (USP) specify six impurities, viz.; impurities A, B, C, D, E and F, respectively for its active pharmaceutical ingredient (API). The identification and synthesis of all impurities except impurity E are well described in the literature; however, there is no report related to impurity E. The prospects to the formation and controlling of impurity E up to ≤0.03% in the synthesis of pantoprazole sodium sesquihydrate (PAN) were discussed in detail for the first time. The present work described the journey towards the successful development of an optimal preparation procedure of dimer impurity E. The most plausible mechanism involved in the formation of impurity E has been proposed.